Penggunaan Metode Read Aloud dalam Pengembangan Berpikir Kritis Anak Usia Dini - Suryani, Lilis; Angela, Ella Nur (Journal of Early Childhood Education (JECE), 2024)
AbstractThe critical thinking of children in Indonesia is still below average. We must take responsibility together. In essence, critical thinking can help children solve problems and make the right decisions in dealing with problems in life. One way to develop critical thinking skills is through the use of the Read Aloud method. This study aims to describe naturally the various situations and conditions that occur and analyze how the use of the Read Aloud method in developing children's critical thinking through storybook reading activities at Bunga Bangsa Kindergarten, Purwakarta, West Java. The research method used is descriptive qualitative with research subjects of children aged 4-6 years. Data analysis used the Miles and Huberman method. The results illustrate that Read Aload can develop children's critical thinking through solutive comments or ideas, the initiative to ask questions and the ability of children to relate the contents of the story to real life.